Studies on the biology of wheat aphids in the Gezira (D. R. Sudan) (Homoptera: Aphididae). - Muddathir, Khalid (Contributions to Entomology = Beiträge zur Entomologie, 1976)
Weekly counts in a wheat field in the central part of the Democratic Republic of Sudan have shown considerable differences in the settling behaviour of Rhopalosiphum maidis (Fitch) and of Schizaphis graminum (Rondani). R. maidis prefers the upper surface of the youngest blades. S. graminum, however, mostly occurs on the upper blade surface, and it aggregates on the blades situated at or near the middle of the plant but is distributed also over the whole plant. The peak infestation of R. maidis takes place during the first half of December on the young wheat plants. The aphid disappears when the wheat ears emerge and the growth of young blades ceases. S. graminum attains its greatest abundance on the wheat about one month later. After the first alatae of the S. graminum had appeared in the wheat fields a rearing experiment was started in a well-ventilated greenhouse. The first born nymphs were used for the further propagation, and 10 t0 12 generations of S. graminum could be attained until the wheat crop was harvested in the field. In connection with these rearing experiments on the duration of the development, the fecundity and the life-span were made.